The Intraocular Pressure-Lowering Effect of Persimmon leaves (Diospyros kaki) in a Mouse Model of Glaucoma - Ahn, Hong Ryul; Yang, Jae Wook; Kim, Jee Young; Lee, Chang Yong; Kim, Tae-Jin; Jung, Sang Hoon (MDPI, 2019)
The aim of this study was to evaluate the pharmacological efficacy of persimmon leaves in two glaucoma models, microbeads-induced ocular hypertension (OHT) and DBA/2 mouse. Thus, we demonstrated that Ethanol Extract of Diospyros kaki (EEDK) reduced elevated intraocular pressure (IOP) in both mouse models of glaucoma by measurements with a tonometer. In particular, we revealed that retinal ganglion cell loss and optic nerve damage caused by IOP elevation were markedly diminished as assessed by TUNEL assay, H&E staining, and fluorescent staining, while the expression of soluble guanylate cyclase (sGC alpha -1) increased, when EEDK was administered, as revealed by western blot. Moreover, the b-wave magnitude indicating functional scotopic vision was significantly improved in EEDK-administered DBA/2 mice during the 10-week follow-up study, as observed with electroretinography. Collectively, our results suggested that EEDK could be an effective therapeutic and IOP-lowering agent for preventing and treating retinal degenerative diseases such as glaucoma.
Keywords: OPEN-ANGLE GLAUCOMA; OCULAR HYPERTENSION; PROSTAGLANDIN ANALOGS; EFFICACY; DEATH